Pengembangan Aplikasi Respons Sms Dan Panggilan Telepon Menggunakan Android Text To Speech Dan Proximity Sensor Bagi Pengemudi Mobil - Mariani Mariani; Herman Tolle; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The use of smartphone in response to incoming message and incoming call while driving may cause the loss of concentration thus increasing the risk of accidents when driving. Many researches had been conducted are using speech recognition to help the driver responds to incoming message and incoming call. However, the response system which using speech recognition can be easily affected by noise disturbance from the road or the vehicle noise so it will be very difficult to receive voice response from the user. So in this research developed a method to receive a response from the user using a proximity sensor to improve accuracy. In this research also used the Android Text to Speech (TTS) system to read aloud incoming message notifications and incoming call for this method to work well in the offline condition. The system is designed to allow users to select message and send message with the keyword module. Furthermore, usability testing for application is conducted using the System Usability Scale (SUS) Questionnaire with usability criteria assessed in the form of efficiency and satisfaction. The result showed an overall SUS value of 76, which indicates that this application as a whole has a good usability.